Earnings dynamics and inequality among men across 14 EU countries, 1994 - 2001: evidence from ECHP - Denisa Maria Sologon; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2009)
This paper analyses the dynamic structure of individual earnings across 14 EU countries over the period 1994-2001 using ECHP. Understanding wage mobility and its link with the evolution of cross-sectional earnings inequality is important from a welfare perspective, particularly given the large variety in national cross-sectional wage inequality. This is highly relevant in the context of the changes that took place in the EU labour market policy framework after 1995 under the incidence of the 1994 OECD Jobs Strategy, which recommend policies to increase wage flexibility, lower non-wage labour costs and allow relative wages to better reflect individual differences in productivity and local labour market conditions. What is the source of earnings variation? Did the increase in cross-sectional wage inequality observed in some countries result from greater transitory fluctuations in earnings and individuals facing a higher degree of earnings mobility? Or is this rise reflecting increasing permanent differences between individuals with mobility remaining constant or even falling? Are there common trends in earnings inequality and mobility across countries? Equally weighted minimum distance methods are used to estimate the covariance structure of earnings, decompose earnings into a permanent and a transitory component and conclude about their evolution. As expected, a notable change was an increased country heterogeneity, which translated itself in the level and evolution of the cross-sectional earnings inequality components. The decrease in cross-sectional inequality was accompanied by an increase in mobility, and therefore a decrease in the importance of the permanent component relative to the transitory component in Denmark, Belgium and Spain, and by a decrease in earnings mobility in Germany, France, UK, Ireland and Austria. In Luxembourg, Italy, Greece, Portugal, and Finland, the increase in cross-sectional inequality was accompanied by a decrease in mobility, whereas in Netherlands by an increase.
urn:nbn:de:101:1-20090304691
Keywords: C23; D31; J31; J60; 330; Panel data; wage distribution; inequality; mobility; Lohnstruktur; Einkommensverteilung; Männer; EU-Staaten